A livre concorrência e as imunidades subjetivas de impostos : reflexões sobre o problema do alcance dessas imunidades - Danilevicz, Thiago (2014)
This paper examines the tax immunity as a possible cause of unbalance to the free competition. For this purpose, it was necessary the study of some general aspects related to the competition, in order to better understand the role of the principle inserted in the article 170, IV, of the Brazilian Federal Constitution. Hence, it was held the analysis of the immunities provided in the article 150, VI, a , b e c and § 4º, of the Federal Constitution, since this article provides that include only the assets, income and services related to the essential purposes of the entities in them mentioned . The issue of the immunity range arises when there is need to know if it is case of restrictive or extensive interpretation. In this last one, the question becomes whether the immunity covers income of the temple , the assets of the temple and temple services .